Characterization of the key odorants and investigation of the effects of drying methods on the aroma, taste, color and volatile profiles of the fruit of Clausena anisum-olens (Blanco) Merr. (1st February 2023) - Luo, Lianfeng; Wang, Jieqiong; Li, Meiqin; Zhang, Yingbin; Wang, Yuwan; Xu, Yongquan; Chen, Haisheng; Zhu, Yan; Feng, Zhihui; Yin, Junfeng
Abstract: With a distinctive aroma, Shanhuangpi (SHP), the fruit of the plant Clausena anisum-olens (Blanco) Merr., has been newly developed as a commercial fruit resource. The fresh fruit deteriorates rapidly due to its high respiration and metabolism. Therefore, an effective drying process is urgently needed for its preservation. The influence of two commonly used drying methods for plant materials, i.e., vacuum freeze-drying (VFD) and hot air drying (HAD) was evaluated on the aroma, taste, color, and volatile profiles of this fruit. The results indicated that the VFD process well retained the color and volatile composition of the fresh fruit but produced extra graininess and sticky mouthfeel. Alternatively, the HAD process offered a shorter drying time, kept a more palatable sour/sweet ratio, but created a darker brown color and shrinking texture of the fruit. The volatile components were enriched by the micro-chamber/thermal extractor (μ-CTE) and 38 compounds were identified with gas chromatography-mass spectrometry. Sixteen odor-active compounds (detection frequency ≥4) were detected by gas chromatography–olfactometry. Results obtained in this study can be served as a reference for the evaluation and further development of SHP. Highlights: Drying process is urgently needed to increase the shelf-life of Shanhuangpi fruit. First study of the impact of drying methods on its sensory and volatiles profiles. The VFD process yielded better preservation of the color and aroma properties. Identified 10 key aroma active compounds of Shanhuangpi fruit.